(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Camellia sinensis is known to mankind centuries back, and the leaves are famous as tea leaves. The huge polyphenolics present in the aerial parts are the key factors for the health benefits. Our current study focussed on evaluating and comparing the influence of various solvents and duration of extraction on the secondary metabolites, antioxidant potential, and in-vitro anti-diabetic activity of the leaves and twigs of C. sinensis. Butanol and methanol were marked effective in the extraction to produce higher yields (45.66%) than other solvents. Duration of extraction also proved to influence the total yield; 48 hours is declared as an optimum duration of time to extract maximum contents from the plant material and proved better in vitro activities and phytoconstituents. Total phenolic and flavonoid contents were identified as higher in 48 hours, whereas total tannins were observed more in 24 hours. Antioxidant activity results performed through 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, phosphomolybdenum method and in vitro anti-diabetic activity results also supported the influence of extraction time and solvents.